A Practical Approach Toward Highly Reproducible and High-Quality Perovskite Films Based on an Aging Treatment - Bai, Xinyu; Kahmann, Simon; Dai, Linjie; Yuan, Shuai; Yin, Shanshan; Heger, Julian E; Schwartzkopf, Matthias; Roth, Stephan V; Chen, Chun-Chao; Zhang, Jianping; Stranks, Samuel D; Friend, Richard H; et al. (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.